The Implementation of Green Housekeeping Management at The St. Regis Bali Resort - I Gede Mangku Setiawan; Ni Nyoman Triyuni; I Ketut Budarma; Dewa Made Suria Antara (Politeknik Negeri Bali, 2021)
This research focuses on analyzing the implementation of green housekeeping management at The St. Regis Bali Resort. The data of the research was collected through observation, interview, questionnaires’ distribution, and documentation. The questionnaires were distributed to the 38 employees of the Housekeeping Department. Quantitative analysis was used to analyze the data. The research results using the frequency distribution of Likert scale with 5 (five) scales on the SPSS version 25.0 stated that the average value of the indicators related to the implementation of green housekeeping management on the questionnaire was a value of 4 or very well implemented. It is proved that the concept of green housekeeping management at The St. Regis Bali Resort has been implemented very well in the daily operations. It aims to preserve the environment, saving energy, and ensure maximum guest satisfaction.